A study on influential factors of occupant window-opening behavior in an office building in China. (April 2018) - Pan, Song; Xiong, Yingzi; Han, Yiye; Zhang, Xingxing; Xia, Liang; Wei, Shen; Wu, Jinshun; Han, Mengjie
Abstract: Occupants often perform many types of behavior in buildings to adjust the indoor thermal environment. In these types, opening/closing the windows, often regarded as window-opening behavior, is more commonly observed because of its convenience. It not only improves indoor air quality to satisfy occupants' requirement for indoor thermal comfort but also influences building energy consumption. To learn more about potential factors having effects on occupants' window-opening behavior, a field study was carried out in an office building within a university in Beijing. Window state (open/closed) for a total of 5 windows in 5 offices on the second floor in 285 days (9.5 months) were recorded daily. Potential factors, categorized as environmental and non-environmental ones, were subsequently identified with their impact on window-opening behavior through logistic regression and Pearson correlation approaches. The analytical results show that occupants' window-opening behavior is more strongly correlated to environmental factors, such as indoor and outdoor air temperatures, wind speed, relative humidity, outdoor PM2.5 concentrations, solar radiation, sunshine hours, in which air temperatures dominate the influence. While the non-environmental factors, i.e. seasonal change, time of day and personal preference, also affects the patterns of window-opening probability. This paper provides solid field data on occupant window opening behavior in China, with high resolutions and demonstrates the way in analyzing and predicting the probability of window-opening behavior. Its discussion into the potential impact factors shall be useful for further investigation of the relationship between building energy consumption and window-opening behavior. Highlights: A real-time monitoring of occupants' window behavior in an office building in China was conducted. Some main influential factors which influence Chinese occupants' window-opening behavior are analyzed. Environmental factors, especially outdoor air temperature and indoor air temperature have significant influence on occupants' window-opening behavior. Some other factors that don't belong to environmental factors also influence occupants' window-opneing behavior to an extent.